METHODOLOGY FOR USING DIGITAL TOOLS IN ACADEMIC WRITING AND SCIENTIFIC RESEARCH - Primqulova Durdona O'tkir qizi; Baydullayeva Feruza Aqilbekovna (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the widespread use and methodology of digital tools in academic writing and research. The main objective of the study is to identify new ways to integrate modern technologies into the research process and the writing process. The study is based on a qualitative analysis and study of various digital platforms, including resource management tools, grammar checkers, and data analysis programs. The results show that digital tools significantly increase the quality, accuracy, and efficiency of academic work by reducing errors, organizing resources, and saving time. In addition, they help researchers avoid plagiarism and maintain academic integrity. At the same time, the results indicate an overreliance on technology and insufficient digital literacy of users.